ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA HAPPY NET SIDOARJO - Firdaus, Septy Dwi Anggraini; Kustiningsih, Nanik (Ekomania, 2023)
Happy Net is a business engaged in printing and selling stationery. The purpose of this study is to analyze whether the cash accounting information system applied to Happy Net is accurate according to the theory of accounting information systems. The data analysis used in this research is descriptive research, namely the analysis technique with data and information collection. The analysis was carried out with information on cash accounting information systems in accordance with documentation, studies and reviews of data and information about cash, outlining cash accounting systems in accordance with existing literature studies. For the company itself, sales are one of the main contents of the company's activities, so sales are important for the survival of the company. If the company does not conduct sales transactions, then the company can be said to be unable to operate properly. Therefore, an adequate sales accounting system is needed to support these activities. The problem discussed in this study is how the application of cash sales accounting information systems in improving the company's internal control can run efficiently and effectively. Seeing from some of the existing problems, the author can provide suggestions for improving the cash sales accounting information system on Happy Net so that it can be more developed and better than before.